Dilmun and its Gulf neighbours - Crawford, Harriet (Cambridge University Press, 1998)
Harriet Crawford presents a scholarly and up-to-date account of the archaeology of the Arabian Gulf from c. 4500-1500 BC. She offers a new interpretation of the structure of the urban, centralized and probably literate society of the Early Dilmun period (c. 2000-1800 BC) using material from the recently excavated site of Saar on the main Bahrain island. Like the neighboring societies in Oman and the Emirates, Dilmun was greatly influenced by its participation in the complex trade routes linking it to Mesopotamia and the Indus Valley.